The impact of brand awareness and electronic word of mouth (e-wom), which are both mediated by brand image, on purchase intent for iPhone smartphone devices - Anggi Yunita Putri Anggi; Firman Firman (Universitas Negeri Padang, 2023)
This study aims to analyze